2020
DOI: 10.3390/app10175801
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Near-Infrared Spectroscopy to Predict Fatty Acid Profile of Meat from Different European Autochthonous Pig Breeds

Abstract: Autochthonous pig breeds provide products of differentiated quality, among which quality control is difficult to perform and insufficient for current market requirements. The present research evaluates the predictive ability of near-infrared (NIR) spectroscopy, combined with chemometric methods as a rapid and affordable tool to assure traceability and quality control. Thus, NIR technology was assessed for intact and minced muscle Longissimus thoracis et lumborum samples collected from 12 European autochthonous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Values of absorbance and the shape of the spectrum are similar to the spectrum of freeze-dried beef reported by Andueza, et al [ 17 ]. The absorbance for freeze-dried beef was lower than the absorbance of fresh beef [ 14 , 17 , 48 ], broiler breast [ 48 ] and pork [ 49 ] but the shape of the spectrum is similar among all the meats. The low absorbance values in the ranges 1440–1470 nm and 1920–1960 nm are due to the absence of water [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Values of absorbance and the shape of the spectrum are similar to the spectrum of freeze-dried beef reported by Andueza, et al [ 17 ]. The absorbance for freeze-dried beef was lower than the absorbance of fresh beef [ 14 , 17 , 48 ], broiler breast [ 48 ] and pork [ 49 ] but the shape of the spectrum is similar among all the meats. The low absorbance values in the ranges 1440–1470 nm and 1920–1960 nm are due to the absence of water [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Calibration and validation statistics of the models are shown in Table 5 and Table 6 . Some authors [ 49 ] reported calibrations for C16:0 and C18:0 with R 2 of 0.66 and 0.71, respectively, in pork using the SNVD and second-order derivatives, while Sierra, et al [ 53 ] and Cecchinato, et al [ 54 ] found that for beef C16:0 and C18:0 FA had an R 2 of 0.8 and 0.7, respectively. These values were similar to those using lamb and beef mixed together [ 14 ] and for rabbit meat [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used NIRS as a rapid method applicable to Iberian pig products (Cáceres-Nevado et al, 2019;Pérez-Marín et al, 2009;Solís et al, 2001;Tejerina et al, 2018;Zamora-Rojas et al, 2012. Overall, these NIRS studies were focused on determining chemical composition, intramuscular fat content and fatty acid profiles, and just few compared intact and minced samples (Cáceres-Nevado et al, 2019;Ortiz et al, 2020;Pérez-Marín et al, 2009). The possibility of determining meat quality traits directly on the intact piece could allow both to avoid meat destruction and to reduce the time required for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors, however, have pointed out that dehydrated samples must be prepared, following procedures that they have developed, as the developed NIR method is not suitable for the samples with high water content. There are a few other recent reports demonstrating the use of a NIR based analysis method for rapid and cost effective identification of crucial nutrients with high precision rates [161]. For example, recently, Miller et al [159] reported a NIR based method for quick assessments of various components of king salmon and greenshell mussels.…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%